4D nano-tomography of electrochemical energy devices using lab-based X-ray imaging. (May 2018) - Heenan, T.M.M.; Finegan, D.P.; Tjaden, B.; Lu, X.; Iacoviello, F.; Millichamp, J.; Brett, D.J.L.; Shearing, P.R.
Abstract: Electrochemical energy devices offer a variety of alternate means for low-carbon, multi-scale energy conversion and storage. Reactions in these devices are supported by electrodes with characteristically complex microstructures. To meet the increasing capacity and lifetime demands across a range of applications, it is essential to understand microstructural evolutions at a cell and electrode level which are thought to be critical aspects influencing material and device lifetime and performance. X-ray computed tomography (CT) has become a highly employed method for non-destructive characterisation of such microstructures with high spatial resolution. However, sub-micron resolutions present significant challenges for sample preparation and handling particularly in 4D studies, (three spatial dimensions plus time). Here, microstructural information is collected from the same region of interest within two electrode materials: a solid oxide fuel cell and the positive electrode from a lithium-ion battery. Using a lab-based X-ray instrument, tomograms with sub-micron resolutions were obtained between thermal cycling. The intricate microstructural evolutions captured within these two materials provide model examples of 4D X-ray nano-CT capabilities in tracking challenging degradation mechanisms. This technique is valuable in the advancement of electrochemical research as well as broader applications for materials characterisation. Graphical abstract: fx1 Highlights: A lab-based 4D nano-CT technique compatible with high temperatures is demonstrated. Identical ROI inspected within two electrode materials between thermal treatments. Metal oxide film growth in SOFCs can increase the pore-phase tortuosity factor. Thermal cycling LiCo O 2 can increase particle size but also lead to cracking.